IMPLEMENTASI ALGORITMA BINARY SEARCH PADA APLIKASI KAMUS INDONESIA-INGGRIS BERBASIS ANDROID - Akmal Nasution; Mohd. Siddik (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
Abstract: The Indonesian-English Dictionary application in this research will be named Kamus Pro, a bilingual Indonesian-English/English-Indonesian dictionary that can be used on Android smartphones. This dictionary application stores data in the form of words and their translations in text files. The main process in the dictionary is the search process. This application will implement a search process based on a binary search algorithm. This algorithm was chosen because the available dictionary data is sorted and the algorithm is easy to implement in Android programming which adopts the Java programming language. Testing of this algorithm uses 2 text file data. The first data is an Indonesian-English text file with a total of 30,450 words. The second data is an English-Indonesian text file containing 23,623 words. Testing will be carried out via an Android emulator on a computer and via an Android smartphone. From the test results, the speed of the search process using a binary algorithm will be recorded, whether testing via an emulator or smartphone directly. The results of this research will later draw conclusions as to the extent of the influence of the application of the binary algorithm on the Dictionary Pro application.Keywords: algoritma; binary search; indonesian english dictionary; android Abstrak: Aplikasi Kamus Indonesia-Inggris dalam penelitian ini akan diberi nama Kamus Pro merupakan kamus dua bahasa Indonesia-Inggris/Inggris-Indonesia yang dapat digunakan pada smartphone android. Aplikasi kamus ini menyimpan data berupa kata dan terjemahannya dalam file teks. Proses utama pada kamus adalah proses pencarian. Aplikasi ini akan menerapkan proses pencarian berdasarkan algoritma pencarian biner (binary). Algoritma ini dipilih karena data kamus yang tersedia sudah terurut serta algoritmanya mudah diimplementasikan pada android programming yang mengadopsi bahasa pemrograman java. Pengujian terhadap algoritma ini menggunakan 2 data file teks. Data pertama file teks indonesia-inggris dengan jumlah kata 30.450. Data kedua file teks inggris-indonesia yang berisi 23.623 kata. Pengujian akan dilakukan melalui emulator android di komputer dan melalui smartphone android. Dari hasil pengujian akan dicatat kecepatan proses pencarian menggunakan algoritma biner, baik pengujian melalui emulator ataupun smartphone langsung. Hasil penelitian ini nanti akan diambil kesimpulan sejauh mana pengaruh penerapan algoritma biner terhadap aplikasi Kamus Pro.Kata kunci: algoritma; binary search; kamus indonesia-inggris; android